Cross‐calibration of different radar systems for monitoring nocturnal bird migration across Europe and the Near East. Issue 5 (4th December 2018) - Liechti, Felix; Aschwanden, Janine; Blew, Jan; Boos, Mathieu; Brabant, Robin; Dokter, Adriaan M.; Kosarev, Vladislav; Lukach, Maryna; Maruri, Mercedes; Reyniers, Maarten; Schekler, Inbal; Schmaljohann, Heiko; et al.
Abstract : Large parts of the continents are continuously scanned by terrestrial weather radars to monitor precipitation and wind conditions. These systems also monitor the mass movements of bird, bat, and insect migration, but it is still unknown how many of these systems perform with regard to detection and quantification of migration intensities of the different groups. In this study that was undertaken within five regions across Europe and the Middle East we examined to what extent bird migration intensities derived from different weather radars are comparable between each other and relate to intensities measured by local small‐scaled radars, some of them specifically developed to monitor birds. Good correspondence was found for the relative day‐to‐day pattern in migration intensities among most radar systems that were compared. Absolute intensities varied between different systems and regions. The findings of this study can be used to infer about absolute bird migration intensities measured by different radar systems and consequently help resolving methodological issues regarding the estimation of migrant numbers in the Western‐Palearctic region. It further depicts a scientific basis for the future monitoring of migratory bird populations across a large spatio‐temporal scale, predicting their movements and studying its consequences on ecological systems and human lives.